Renewable-juglone-based high-performance sodium-ion batteries - Wang, Hua (2015)
A renewable-biomolecule-based electrode is developed through a facile synchronous reduction and self-assembly process, without any binder or additional conductive agent. The hybridized electrodes can be fabricated with arbitrary size and shape and exhibit superior capacity and cycle performance. The renewable-biomaterial-based high-performance electrodes will hold a place in future energy-storage devices.